2022
DOI: 10.1186/s13071-022-05224-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, genetic characterization and molecular phylogeny of the poorly known nematode parasite Cissophyllus leytensis Tubangui & Villaamil, 1933 (Nematoda: Ascaridida) from the Philippine sailfin lizard Hydrosaurus pustulatus (Eschscholtz, 1829) (Reptilia: Squamata)

Abstract: Background The genus Cissophyllus (Cosmocercoidea: Kathlaniidae) is a rare group of nematodes parasitic in turtles and lizards. To date, only four species have been reported in Asia and North America. However, most of them are inadequately described. The species Cissophyllus leytensis has never been reported since it was originally described by Tubangui and Villaamil in 1933 from the Philippine sailfin lizard Hydrosaurus pustulatus (Eschscholtz, 1829) (Reptilia: Squamata). Furthermore, the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In Rhigonematomorpha, only 21 nominal species have been genetically characterized [14-17, 19, 20], and most of the data available are represented by the 18S and 28S sequences, which are commonly used for molecular phylogeny of higher taxa within Nematoda [21][22][23][24][25][26]. Although the nuclear internal transcribed spacer (ITS) region and the mitochondrial cox1 and cox2 genes are widely used as powerful and practical genetic markers for revealing sibling or cryptic species, delimiting phenotypic variation and identifying species in the infraorders Ascaridomorpha, Spiruromorpha and Oxyuridomorpha [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], they have been scarcely employed in studies pertaining to Rhigonematomorpha species. Consequently, no current knowledge on the effectiveness of ITS, cox1 and cox2 as genetic markers for identification of Rhigonematomorpha nematodes is available.…”
Section: Introductionmentioning
confidence: 99%
“…In Rhigonematomorpha, only 21 nominal species have been genetically characterized [14-17, 19, 20], and most of the data available are represented by the 18S and 28S sequences, which are commonly used for molecular phylogeny of higher taxa within Nematoda [21][22][23][24][25][26]. Although the nuclear internal transcribed spacer (ITS) region and the mitochondrial cox1 and cox2 genes are widely used as powerful and practical genetic markers for revealing sibling or cryptic species, delimiting phenotypic variation and identifying species in the infraorders Ascaridomorpha, Spiruromorpha and Oxyuridomorpha [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], they have been scarcely employed in studies pertaining to Rhigonematomorpha species. Consequently, no current knowledge on the effectiveness of ITS, cox1 and cox2 as genetic markers for identification of Rhigonematomorpha nematodes is available.…”
Section: Introductionmentioning
confidence: 99%
“…The monophyly of the Cosmocercidae family has been corroborated by several studies (Tran et al, 2015;Sinsch et al, 2019;Sinsch et al, 2020;Ni et al, 2022); nonetheless, due to the low sampling of taxa, geographic limitations and few molecular data available, the phylogenetic relationships between the genera of the family are still unclear. Sinsch et al (2020) and Chen et al (2020) during phylogenetic studies, using the 18S and internal transcribed spacer 1 ribosomal markers, demonstrated that the genera Cosmocerca and Cosmocercoides are phylogenetically close related.…”
Section: Discussionmentioning
confidence: 93%
“…The monophyly of the Cosmocercidae family has been corroborated by several studies (Tran et al ., 2015 ; Sinsch et al ., 2019 ; Sinsch et al ., 2020 ; Ni et al ., 2022 ); nonetheless, due to the low sampling of taxa, geographic limitations and few molecular data available, the phylogenetic relationships between the genera of the family are still unclear. Sinsch et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed morphological identification on nematodes obtained from 93 captive and 11 wild PHs. The lactophenol clarification procedure was conducted as previously described [ 26 ]. All strongylids were classified based on the morphological characteristics outlined by Lichtenfels et al [ 8 ] and Zhang and Kong [ 10 ].…”
Section: Methodsmentioning
confidence: 99%